Rekonstruksi Konsep Keberlanjutan dalam Perhutanan Sosial: Perspektif Etika Ekosentris - Faiza Libby Shabira Lubis; Muhammad Sarjan (Mataram University, 2026)
Forest sustainability in Indonesia faces significant challenges, including deforestation, forest degradation, and tenure conflicts. Although social forestry has been promoted as a policy instrument to balance ecological protection and community welfare, its implementation remain largely dominated by an anthropocentric paradigm that treats forest primarily as economic resources. As a result, sustainability is often interpreted narrowly and fails to adequately address broader ecological and social concerns. Moreover, studies examining social forestry through an ecocentric ethical perspective remain limited, indicating a conceptual gap in developing more holistic forest management models.This Study aims to reconstruct the concept of sustainability in social forestry based on an ecocentric ethical perspective and to explore its policy implications. A narrative literature review with a conceptual approach was employed, analyzing relevant publications form 2015 to 2025. The finding reinforce the core argument: achieving sustainability in social forestry requires an ecocentric shift that recognizes forests’ intrinsic value. This new framework integrates ecological and cultural capacity indicators, incorporates intrinsic value in licensing, and strengthens participatory governance with ecological justice. This study contributes a novel conceptual framework that is both integrative and operational for advancing more equitable, adaptive, and sustainable social forestry practices.